Peran Elemen Kemasan Terhadap Perilaku Pembelian Kopi Instan Sachet - Lina Budiarti (Akutansi Bisnis & Manajemen ( ABM ), 2017)
This study aimed to determine the role of packaging elements, such as packaging color, background image, font style, printed information, and innovation toward instant coffee sachet buying behavior. Meanwhile, the data was collected by distributing questionnaires to 120 college students of Business Administration in State Polytechnic of Malang that are selected through purposive sampling technique. Data analysis techniques used in this study is the Structural Equation Modeling (SEM). The findings of the study show that the packaging color, background image, font style, printed information, and innovation have positive influence on instant coffee sachet buying behavior.